ABORSI SEBAGAI PERBUATAN KRIMINAL DIKAITKAN DENGAN KITAB UNDANG-UNDANG HUKUM PIDANA DAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Yanti Agustina Manik (jurnal.unprimdn.ac.id, 2019)
In terms of the term abortion means the termination of pregnancy before the fetus can grow outside the mother’s body. Abortion can be divided into two, namely spontaneous abortion and artificial abortion. Artificial abortion subdivided based on reason, namely abortion medisinalis and abortion criminalist. Abortion is a criminal act. Based on Penal Code abortion is prohibited in Indonesia but based on the Law No.36 of 2009 stated that abortioncould be done with certain conditions. Differences abortion regulation lawsbased on the Law No.36 of 2009 and Penal Code were mediated by the principle of “lex posteriori derogat legion priori” which made an issue on abortion regulation lawsonly in medical emergency namely” provokatus medicalis.